设函数[img=81x25]1802da75d8167e3.png[/img]由方程[img=158x42]1802da75df9f6d0.png[/img]所确定,则[img=200x47]1802da75e988eff.png[/img]=________
举一反三
- 设函数z = z(x,y)由方程[img=92x39]1803d35288999b2.png[/img]确定,其中F为可微函数,且[img=58x27]1803d352917a342.png[/img],则[img=134x47]1803d35299ebd2a.png[/img] A: 0 B: x C: -z D: z
- 设方程[img=134x19]17e43d6cf7199ff.jpg[/img]确定了y是x的函数y=f(x),则f''(x)=( ) 未知类型:{'options': ['', ' [img=96x37]17e43d6d0875b49.jpg[/img]', ' [img=74x38]17e43d6d116f70e.jpg[/img]', ' [img=83x37]17e43d6d1ab1472.jpg[/img]'], 'type': 102}
- 设函数y=f(x)由参数方程[img=164x19]17da62a295a4708.jpg[/img]所确定,则[img=19x34]17da4275482315f.jpg[/img]为 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 设函数[img=85x21]17e0c068af3d847.jpg[/img],则[img=62x20]17e0c068bc121fb.jpg[/img] A: 25 B: 50 C: 75 D: 100
- 设f(u)是可导函数,方程[img=126x27]18039625682b2d9.png[/img]确定z=z(x,y),则[img=76x23]180396257044024.png[/img] A: x B: y C: z D: xy E: xyz